China–EU Energy Security Cooperation: The Case for Renewables - Garlick, Jeremy (Power Shifts in East Asia and Their Implications for Asia–Europe Relations, 2019)
The idea of China and the European Union cooperating on energy security is one which may not seem logical or likely at first glance. The two actors are geographically distant from one another and their energy supply needs and routes do not intersect for the most part. Yet careful study of the possibilities reveals that there is not only the potential, but also the need for cooperation on energy security. This is particularly the case in the field of renewables, where there is an opportunity to achieve win-win synergies which can produce enhanced outcomes in terms of local and global energy production and consumption. Financial support for this article was provided by the Internal Grant Agency of the Faculty of International Relations, University of Economics, Prague, as part of the research project “The New Silk Road Initiative as a New Stage of Chinese Global Activity,” project no. F2/32/2017.